PENGARUH LINGKUNGAN KERJA DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PDAM TIRTANADI SUMATERA UTARA MEDAN - ARASY AYU SETIAMY (LP2MTBM MAKARIOZ, 2019)
An organization in carrying out its activities to achieve its goals has several factors that are mutually bound and influential. One of the most important factors used to drive other factors is human resources. Therefore, the organization is required to manage and optimize human resources. Management of human resources itself is very important in a company in addition to other factors such as capital. Because the management of Human Resources itself to get a reliable employee and able to carry out their duties properly and responsibilities that can improve the effectiveness of the organization in order to achieve the goal.The purpose of this study is to know that the work environment and discipline to give effect to the performance of employees in PDAM Tirtanadi North Sumatra Medan either partially or simultaneously. The population of this study is all employees who work in the company. Where samples taken in this study were as many as 91 people. Data were collected using observations and questionnaires. Data are tested using validity and reliability tests, and the data must satisfy the classical assumption test element. Furthermore, data analysis is done by using multiple regression analysis, t test, F test, and coefficient of determination.This research concludes that there is influence of Work Environment on Employee Performance in PDAM Tirtanadi Medan. There is influence of Work Discipline on Employee Performance at PDAM Tirtanadi Medan. There is influence of Work Environment and Work Discipline on Employee Performance at PDAM Tirtanadi Medan. This is based on the criteria of conclusion that shows the value of tcount is greater than the value of ttable with the probability value is smaller than the value of Alphanya. The amount of work environment and work discipline ability to explain the performance is 0.236 or 23.6% while the remaining 76.4% is explained by other variables not included in this research model.